The governance of human trafficking in Egypt: The legal, policy, and institutional frameworks - Abdel Aziz, Nourhan Amr (AUC Knowledge Fountain, 2016)
Human trafficking is the third largest and fastest growing organized crime in the world after drug trafficking and illicit arms dealing. According to the International Labor Organization, there is an estimated 2.4 million trafficked individuals at any given moment in time. As many as 1.2 million of the 2.4 million are minors. Out of the 2.4 million trafficked individuals, UNODC points out that 230,000 are in the Middle East and North Africa region. Egypt is a country of origin, transit, and destination for trafficking. Yet, the literature available regarding Egypt’s response to the growing phenomenon of human trafficking is minimal. As a result, this study explores Egypt’s governance of trafficking in persons in order to reflect on the effectiveness of its response to the crime. This dissertation provides a comprehensive analysis of the legal, policy, and implementation frameworks of human trafficking in Egypt. It is divided into eight chapters. The first chapter serves as an introduction and provides background information on trafficking in persons. Chapter II outlines the methodology for this thesis. Chapter III discusses the flows, magnitude, and directions of trafficking in Egypt. Chapter IV explores the theoretical framework that dominates the study of human trafficking. It points out its limitations and argues that it influenced the development of the legal system of trafficking. The following chapter analyzes the emergence of the current legal framework of trafficking on an international level and showcases how the theoretical framework has influenced it. Its analysis is important to understand how its limitations has been translated down to the national level in the case of Egypt. Chapter VI explains Egypt’s policy on human trafficking in terms of actors, drivers, and strategies. It also provides a comprehensive critique of the policy development process and its design. Chapter VII analyses the implementation mechanisms of anti-trafficking policies in Egypt . Lastly, Chapter VI provides the general conclusions of the study.